Hemophilia Care in Italy - Mannucci, P. M; Ruggeri, Z. M (Thrombosis and Haemostasis, 1976)
Twenty specialized centres for the care of hemophilia and allied disorders have now been established in Italy. Their geographic distribution is uneven and the number is considered inadequate. Financial support is provided by regional Health Departments or by University and General Hospitals; a bill recognizing hemophilia as a social disease entitles the centres to an annual grant from the State or Regional Boards. Less than half of factor VIII employed in the management of hemophilia A is supplied as a cryoprecipitate from hospital blood banks; the rest is imported from commercial manufacturers who also satisfy all the demand for prothrombin complex concentrates. Commercial freeze-dried concentrates can also be obtained free of charge at pharmacies by hemophiliacs covered by national social security schemes. This arrangement facilitates home treatment, which appears the ideal form of management in a country with the geographical features of Italy. In Lombardy, a bill allows hemophiliacs or their relatives to give infusions after adequate instruction. All this has been a great help in achieving more modern management of hemophilia; however, dependence on imported commercial concentrates appears unreasonable on a long-term basis, and major efforts should be directed towards developing a national program for manufacturing blood components.